Analisis Kesalahan Siswa SMA Dalam Menyelesaikan Soal Materi SPLTV Berdasarkan Prosedur Kastolan - Putra, Muhammad Alde; Suanto, Elfis; Hutapea, Nahor Murani (Media Pendidikan Matematika, 2026)
Previous studies have applied the Kastolan error analysis procedure to identify students’ errors in solving mathematics problems. However, most studies have focused on prerequisite topics, particularly Systems of Linear Equations in Two Variables (SPLDV), or have examined students’ errors in Systems of Linear Equations in Three Variables (SPLTV) based on specific characteristics, such as prior ability and gender. Consequently, comprehensive information regarding the general error patterns of senior high school students in solving SPLTV problems based on the Kastolan procedure remains limited. This study aims to analyze the errors made by high school students in solving SPLTV questions based on Kastolan’s error analysis procedure, which includes conceptual, procedural, and technical errors. This study uses a qualitative descriptive method with 18 tenth-grade students at SMAIT Tahfizh Al-Fatih Pekanbaru as the research subjects. Data were collected through an essay test consisting of two contextual SPLTV questions. The results of the analysis show that technical errors (49.1%) in the fairly high category were the most frequent errors, followed by procedural errors (47.3%) in the fairly high category and conceptual errors (3.6%) in the very low category. The results of this study indicate that procedural and technical errors are the most common errors made by students in solving SPLTV questions, so educators need to pay attention to this so that these errors can be avoided in every mathematics question.